2019
DOI: 10.3390/cancers11091393
|View full text |Cite
|
Sign up to set email alerts
|

Should Tumor Infiltrating Lymphocytes, Androgen Receptor, and FOXA1 Expression Predict the Clinical Outcome in Triple Negative Breast Cancer Patients?

Abstract: Tumor-infiltrating lymphocytes (TILs) are a valuable indicator of the immune microenvironment that plays the central role in new anticancer drugs. TILs have a strong prognostic role in triple negative breast cancer (TNBC). Little is known about the interaction with the androgen receptor (AR) and forkhead box A1 (FOXA1). We analyzed the relationships between TIL levels, AR, and FOXA1 expression and their clinical significance in TNBC patients. Further, we investigated their interaction with other biomarkers lik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Recent scientific research is emerging to identify novel prognostic biomarkers for targeted analysis and therapy of TNBCs [ 55 ]. PD1 is an immune checkpoint receptor and a cardinal immunosuppression mechanism used by cancer cells to escape host immunity [ 55 ]. Its ligand, PDL1 predicted AR positivity, as AR-positive TNBC was threefold more likely to express PD-L1 on cancer cells.…”
Section: Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent scientific research is emerging to identify novel prognostic biomarkers for targeted analysis and therapy of TNBCs [ 55 ]. PD1 is an immune checkpoint receptor and a cardinal immunosuppression mechanism used by cancer cells to escape host immunity [ 55 ]. Its ligand, PDL1 predicted AR positivity, as AR-positive TNBC was threefold more likely to express PD-L1 on cancer cells.…”
Section: Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…FOXA1 is a key determinant of ER function and endocrine response. There is a significant association between AR and FOXA1 status [ 55 , 58 ]. In one study, co-expression of AR and FOXA1 was found in 15% of all TNBCs [ 26 ] and it was associated with shorter DFS [ 55 ].…”
Section: Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…To date, there are no targeted therapies available for patients with advanced TNBC (84). This subgroup of tumors represents a very heterogeneous disease, consisting of a wide spectrum of biologically distinct subtypes with different prognosis (85). TNBC harbors a specific inflammatory microenvironment in which high levels of molecules released from activated inflammatory cells, such as pro-inflammatory cytokines, ROS, reactive nitrogen species (RNS), coexist with angiogenic factors, such as the Vascular Endothelial Growth Factor (VEGF), and with a significant amount of Tumor-Infiltrating Lymphocytes and TAMs (86).…”
Section: Tnbc: An Open Challenge In Preclinical Studiesmentioning
confidence: 99%
“…TNBC is the most immunogenic breast cancer subtype; an increasing number of PD-L1 expression levels and immune checkpoint inhibitors have been emerging as potential therapeutic options for TNBC. A previous study has provided information on the prognosis of tumor-infiltrating lymphocytes (TILs), androgen receptor (AR), and forkhead box A1 (FOXA1) in TNBC [ 14 ]. In the study, patients with low TIL scores exhibited low survival and the combination of TIL levels and AR or FOXA1 expression affected the clinical outcome [ 14 ].…”
Section: Breast Cancermentioning
confidence: 99%
“…A previous study has provided information on the prognosis of tumor-infiltrating lymphocytes (TILs), androgen receptor (AR), and forkhead box A1 (FOXA1) in TNBC [ 14 ]. In the study, patients with low TIL scores exhibited low survival and the combination of TIL levels and AR or FOXA1 expression affected the clinical outcome [ 14 ]. In another study, a gene expression profiling meta-analysis revealed novel gene signatures related tyrosine kinase in TNBC [ 15 ].…”
Section: Breast Cancermentioning
confidence: 99%